Enhanced Recovery after Surgery (ERAS) in Gynecology: State of the Art and the Problem of Barriers - Sara Forte; Filippo Alberto Ferrari; Hooman Soleymany Majd; Francesca Cisotto; Federico Ferrari (IMR Press, 2023)
Objectives: The advantages of the enhanced recovery after surgery (ERAS) protocols application in all surgical branches have been largely demonstrated, even though there is a lack of a strong evidence from randomized trial and the evidence regarding the multimodality treatments is of low grade. Moreover, the problem of the barriers to the implementation of these protocols in clinical practice remains an unsolved problem. Mechanism: We performed a narrative review reporting the main barriers and enablers on the subject. Finding in Brief: The main barriers are resistance to change, lack of support from institutions and of financial resources or manpower, poor communication and collaboration within the multidisciplinary team, organizational problems, lack of standardized protocols, patient-related barriers (individual factors, reluctance, or inadequate education) and lastly clinical practice in small community hospitals. To overcome these problems, several enablers have been identified including: the involvement of the patient, the reorganization of care systems through standardized ERAS protocols, identification of a leader/coordinator, promotion of teamwork and staff education, financial resources, and the recognition of the role of the professionals involved. Conclusions: At this moment, resistance to change remains the most frequent and difficult barrier to overcome and, in our opinion, a reorganization of the health system aiming to the implementation of the ERAS protocols in the clinical practice is required.